2022
DOI: 10.1037/pas0001120
|View full text |Cite
|
Sign up to set email alerts
|

The Four-Item Mentalising Index (FIMI) is a valid, reliable, and practical way to assess mentalising: Reply to Murphy et al. (2022).

Abstract: Murphy et al. (2022) raised concerns regarding the validity of the Four-Item Mentalising Index (FIMI). We wholeheartedly agree with Murphy et al. that there are problems in the social cognition literature hampering research. However, we maintain the FIMI is conceptually grounded in empirical and theoretical research, and that concerns regarding its construct validity are overstated. Drawing on recent research, we also discuss issues concerning the interpretation of discriminant validity analyses and discuss ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Multiple regression analysis confirmed that sex, education, and adjusted income uniquely predicted ToM, but age and political beliefs did not predict ToM ( F [ 5 , 4066] = 27.21, p < .001, R 2 = .03; Table 3 ). Averaging across models, Bayesian modelling revealed that the data provided strong support for sex and education predicting ToM, and anecdotal support for adjusted income predicting ToM.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Multiple regression analysis confirmed that sex, education, and adjusted income uniquely predicted ToM, but age and political beliefs did not predict ToM ( F [ 5 , 4066] = 27.21, p < .001, R 2 = .03; Table 3 ). Averaging across models, Bayesian modelling revealed that the data provided strong support for sex and education predicting ToM, and anecdotal support for adjusted income predicting ToM.…”
Section: Resultsmentioning
confidence: 89%
“…Measuring ToM, however, is not straightforward. Issues in the validity, reliability, and practical utility of existing measures (e.g., [ 3 , 4 ]), as well as differences in conceptualisations of ToM (e.g., [ 5 ]) have hampered ToM research designs, sample sizes, and the validity of some existing findings. ToM measures also do not typically correlate well with each other (e.g., [ 6 ]) suggesting they may be measuring divergent constructs.…”
Section: Introductionmentioning
confidence: 99%
“…Items 5, 6, and 7 also tap into challenges with theory of mind (ToM), the ability to understand others’ minds. Interestingly, these items with greatest centrality in the AQ10 broadly correspond with the Four-Item Mentalising Index, a recently developed self-report measure of ToM (Clutterbuck et al, 2021; 2022). Our findings suggest the possibility that ToM-associated differences are key markers for indicating overall levels of autistic traits, aligning with theories that ToM differences are crucial for understanding autism (Livingston et al, 2019; 2021; Livingston & Happé, 2021).…”
Section: Discussionmentioning
confidence: 96%
“…The DEP is being used to refer to various constructs (i.e., jingle), as well as different concepts referred to as double empathy (i.e., jangle). This problem is not unique to the DEP and reflects a wider problem in social cognition research (e.g., Clutterbuck et al, 2021Clutterbuck et al, , 2022Murphy et al, 2022;Quesque & Rossetti, 2020), including the empathy literature specifically (see Olderbak & Wilhelm, 2020, for detailed discussion). Across a range of studies, the term "DEP" is used, despite explicitly describing and measuring a range of entirely different social cognitive constructs.…”
Section: Fuzzy Theoretical Conceptmentioning
confidence: 99%